Proteasome Dependent Actin Remodeling Facilitates Antigen Extraction at the Immune Synapse of B Cells - Ibañez-Vega, Jorge; Del Valle Batalla, Felipe; Saez, Juan José; Soza, Andrea; Yuseff, Maria-Isabel (Frontiers in Immunology, 2019)
Engagement of the B cell receptor (BCR) with surface-tethered antigens leads to the formation of an immune synapse (IS), where cell signaling and antigen uptake are tightly coordinated. Centrosome re-orientation to the immune synapse has emerged as a critical regulatory step to guide the local recruitment and secretion of lysosomes, which can facilitate the extraction of immobilized antigens. This process is coupled to actin remodeling at the centrosome and at the immune synapse, which is crucial to promote cell polarity. How B cells balance both pools of actin cytoskeleton to achieve a polarized phenotype during the formation of an immune synapse is not fully understood. Here, we reveal that B cells rely on proteasome activity to achieve this task. The proteasome is a multi-catalytic protease that degrades cytosolic and nuclear proteins and its dysfunction is associated with diseases, such as cancer and autoimmunity. Our results show that resting B cells contain an active proteasome pool at the centrosome, which is required for efficient actin clearance at this level. As a result of proteasome inhibition by MG-132, activated B cells do not deplete actin at the centrosome and are unable to separate the centrosome from the nucleus and thus display impaired polarity. Consequently, lysosome recruitment to the immune synapse, antigen extraction and presentation are severely compromised in B cells with diminished proteasome activity. Additionally, we found that proteasome inhibition leads to impaired actin remodeling at the immune synapse, where B cells display defective spreading responses and distribution of key signaling molecules at the synaptic membrane. Overall, our results reveal a new role for the proteasome in regulating the immune synapse of B cells, where the intracellular compartmentalization of proteasome activity controls cytoskeleton remodeling between the centrosome and synapse, with functional repercussions in antigen extraction and presentation.